Rebecca - Du Maurier, Daphne, 1907-1989. (New York : Avon Books, 1971)
For months after her death, the memory of Rebecca de Winter continues to dominate everyone at her former home, Manderley, one of the most famous English country houses.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Book Links (A.L.A.), January 1999.
Booklist, August 1997.
Notable/Best Books (A.L.A.), February 2007.
Keywords: Country homes -- England -- Cornwall (County) -- Fiction; Man-woman relationships -- Fiction; Love stories; Man-woman relationship -- Fiction; Romantic suspense novels; Cornwall (England : County) -- Fiction; Cornwall (England : County) -- Fiction; Romantic suspense novels